THEORETICAL APPROACH TO ONLINE MARKETING - Durmaz, Assist. Prof. Yakup; Ä°lhan, Ahmet; Ince, Ercan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The Internet is one of the first things leading technological developments. It provides easy accessibility to the products. These kind of developments led businesses to use the Internet intensely in marketing. Thus, online marketing has started to develop and become one of the direct marketing techniques. Online marketing provides both businesses and customers with a great deal of easiness. Companies present customers with products, services and information in an untraditional way thanks to online marketing. Moreover, customers have had the advantage of following the developments and changes, also the access to the products and services easily. Other than the power of information access of the Internet, commerce network and distribution have appeared to be very efficient. In this regard, online marketing have been considered to be one of the tools of modern marketing in terms of reaching customers.Â 